2019
DOI: 10.7150/ntno.38954
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced blood-brain-barrier penetrability and tumor-targeting efficiency by peptide-functionalized poly(amidoamine) dendrimer for the therapy of gliomas

Abstract: Glioblastoma is one of the most common primary tumor types of central nervous system (CNS) with high malignance and lethality. Although many treatment options are currently available, the therapy of brain cancers remains challenging because of blood-brain-barrier (BBB) which prevents most of the chemotherapeutics into the CNS. In this work, a poly(amidoamine) dendrimer-based carrier was fabricated and modified with angiopep-2 (Ang2) peptide that has been demonstrated to bind to low density lipoprotein receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 65 publications
0
41
0
Order By: Relevance
“…Furthermore, PAMAM was concurrently functionalized with an EGFR-targeting peptide (EP-1) to achieve specificity and improved affinity to target EGFR. The above results showed the potential of the dual drug-loaded PAMAM in the treatment of gliomas by improving BBB penetration and specific EGFR targeting efficiency, both in vitro and in vivo ( Figure 6 ) [ 148 ].…”
Section: Current Pharmaceutical Drug Targets In Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PAMAM was concurrently functionalized with an EGFR-targeting peptide (EP-1) to achieve specificity and improved affinity to target EGFR. The above results showed the potential of the dual drug-loaded PAMAM in the treatment of gliomas by improving BBB penetration and specific EGFR targeting efficiency, both in vitro and in vivo ( Figure 6 ) [ 148 ].…”
Section: Current Pharmaceutical Drug Targets In Gliomamentioning
confidence: 99%
“… ( A ) Schematic representation of fabrication of the dual drug loaded polyamidoamine (PAMAM) dendrimers in the treatment of gliomas by improving BBB penetration; ( B ) Assessment of the affinity and specificity of peptide EP-1 toward EGFR; ( C ) In vitro evaluation of biocompatibility and anti-tumor efficacy of the dual drug-loaded PAMAM dendrimers; ( D ) Flow cytometry evaluation for intracellular uptake of different DOX-loaded dendrimers. Reprinted from [ 148 ] Ivyspring International Publisher, 2020. * p < 0.1, ** p < 0.01, *** p < 0.001, **** p < 0.0001 (Student’s t -test).…”
Section: Figurementioning
confidence: 99%
“…DGL-PEG-T7/DNA NPs showed extraordinary gene silencing activity and dual-targetability to BBB as well as glioma cells expressing TfRs. Unlike such TfR-targeted nanoparticles, the PAMAM dendrimers synthesized by Liu et al simultaneously recruited two different ligands, angiopep-2 (Ang2) and epidermal growth factor receptor (EGFR)-targeting peptide (EP-1), to achieve the dual-targetability [ 104 ]. Ang-2 peptides are specific ligands binding with lipoprotein receptor-relative protein-1 (LRP1) on endothelial cells of BBB.…”
Section: Dendrimersmentioning
confidence: 99%
“…[ 80,85,93,99–101 ] Groups have shown that nanoparticles with targeting moieties binding to these ligands exhibit significant increase in specificity and uptake by GBM cells ≈13‐fold (Tf‐R), ≈1.4‐fold (EGFR), ≈3.5‐fold (Fn14), and ≈2.3‐fold (LRP‐1) when compared to controls without the moiety. [ 85,99–101 ] It is important to note that this variation between targeting ligands may be due to the preclinical model used and mode of nanoparticle delivery (systemic vs local), but regardless, improved targeting is evident and can be further optimized with combinations of moieties. Nanoparticle systems have also been designed that respond to environmental conditions such as pH and the presence of certain enzymes that are unique to the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%